Neuraminidase Inhibitors and Hospital Length of Stay: A Meta-analysis of Individual Participant Data to Determine Treatment Effectiveness Among Patients Hospitalized With Nonfatal 2009 Pandemic Influenza A(H1N1) Virus Infection - Venkatesan, Sudhir (2019)
Fil: Venkatesan, Sudhir. Division of Epidemiology and Public Health, Nottingham; Inglaterra.